Physico-chemical and functional properties of native and hydrolyzed kidney bean (Phaseolus vulgaris L.) protein isolates. (October 2015) - Wani, Idrees Ahmed; Sogi, Dalbir Singh; Shivhare, Uma Shanker; Gill, Balmeet Singh
Abstract: The study was carried out to analyze the effect of papain hydrolysis on the physico-chemical and functional properties of kidney bean protein isolates. The protein isolates were prepared from four kidney bean cultivars by alkali solubilization and isoelectric precipitation. Yield of protein isolates on seed weight basis varied significantly (p ≤ 0.05) between 16.89 and 20.50%. Native protein isolates revealed moisture, protein, fat and ash in the range of 7.38–9.55 g/100 g, 76.96–80.04 g/100 g, 2.53–3.44 g/100 g and 4.32–4.57 g/100 g, respectively. Protein isolates were subjected to proteolysis using papain at a concentration of 0.01 g/10 g of protein isolate for 30 and 60 min. Degree of hydrolysis of kidney bean protein isolates varied from 3.13 to 4.70% for 30 min treatment and 6.71–8.63% for 60 min treatment. Thermal properties of native and hydrolyzed kidney bean protein isolates showed two endothermic transitions. Hydrolyzed protein isolates had lower transition temperatures and enthalpy of denaturation than native counterparts indicating hydrolysis of proteins. Protein solubility, water and oil absorption capacity increased significantly on proteolysis. Emulsifying properties measured as emulsifying activity index and emulsifying stability index increased significantly on proteolysis. Foaming capacity of native kidney bean protein isolates in the pH range of 2–10 varied from 46.0 to 126.0% and it increased significantly on hydrolysis from 54.9 to 151.1%. Highlights: Native kidney bean protein isolates showed significant differences in composition. Native protein isolates had very good functional properties. Proteolysis of protein isolates using papain for 30 and 60 min was performed. Functional properties of protein isolates improved significantly on proteolysis.